Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/jper.20-0056
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of retrograde peri‐implantitis in sites with previous apical surgeries: A retrospective study

Abstract: Background Retrograde peri‐implantitis (RPI) is a rapidly progressing periapical infection that forms around the implant apex. It is usually associated with sites adjacent to teeth with apical lesions; previous endodontic failures, retained root fragments, etc. This study aimed to study the incidence of RPI in sites with a history of apical surgeries. Methods Patients with sites treated for both apicoectomy and implant placement presenting to the University of Michigan School of Dentistry from 2001 to 2016 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Lefever et al [ 23 ] showed a much higher incidence, with around 14% of the cases adjacent to teeth with PAL showing RPI. Another study showed that sites with previous endodontic failure and apical surgery show RPI in 20% of the cases [ 29 ]. In the present study, the sites with previous endodontic involvement did not show an increased risk of RPI.…”
Section: Discussionmentioning
confidence: 99%
“…Lefever et al [ 23 ] showed a much higher incidence, with around 14% of the cases adjacent to teeth with PAL showing RPI. Another study showed that sites with previous endodontic failure and apical surgery show RPI in 20% of the cases [ 29 ]. In the present study, the sites with previous endodontic involvement did not show an increased risk of RPI.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the odds of developing early IPL in implant sites with apical lesion was up to 26.3-fold [14]. However, recent retrospective study including 25 patients showed that previous endodontic surgery in implant site did not increase risk of IPL [41].…”
Section: Patient-associated Factorsmentioning
confidence: 99%
“…This implant disease was first described by McAllister et al [ 17 ] in 1992 and seems to have an incidence ranging from 0.26% to 1.86% [ 18 , 19 , 20 , 21 ], significantly lower than marginal peri-implantitis. Although the etiology of this lesion is still unclear [ 22 ], according to several authors, the causes more accredited could be the residual infection/inflammation of the tooth replaced by the implant or the endodontic lesion of neighboring teeth [ 13 , 23 , 24 ]. Among other factors hypothesized, there are bone overheating or implant insertion in a site with residual granulomatous/cystic lesions [ 22 ].…”
Section: Introductionmentioning
confidence: 99%